Use of high-density EEG in patients with Parkinson's disease treated with deep brain stimulation - Buril, Jiri; Burilova, Petra; Pokorna, Andrea; Balaz, Marek (Biomedical papers, 2020)
The number of reports on cognitive changes related to deep brain stimulation (DBS) surgery in Parkinson's disease (PD) is growing. The aim of the review was to assess whether high-density electroencephalography (HD EEG) in patients with DBS treatment for PD is used and mentioned as a research method for the assessment of cognitive function changes after DBS of the subthalamic nucleus. The HD EEG examination method demonstrates the effects of DBS on changes of connectivity among various areas of the brain using changes in bioelectric potentials recorded on the scalp during examination. The search results yielded seven studies on the possibility of using HD EEG to investigate changes in bioelectric potentials with various protocols (motor tasks, auditory stimuli). Based on the results, HD EEG appears to be a feasible research method in patients with PD and established DBS therapy. Therefore, we plan to use HD EEG to demonstrate the effects of DBS on changes of connectivity among various areas of the brain utilizing changes in bioelectric potentials recorded on the scalp during HD EEG examination.
Keywords: Parkinson's disease; deep brain stimulation; high density; electroencephalography; cognitive changes